Influence of management systems on the nitrogen mineralization and fertilization of sugarcane (2016)
In Colombia, nitrogen fertilizer recommendations for sugarcane are based on data obtained with the Walkey and Black method, but they do not always result in the best yield. In this sense, the present study aimed to compare the results of the determination of fast mineralizable nitrogen (amino sugars), performed with the Illinois Soil Nitrogen test (ISNT) and Direct Steam Distillation method (DSD) for nitrogen recommendations for crops. A complete randomized block design was used with six treatments, adding nitrogen through urea and compost to Pachic haplustoll soils in Valle del Cauca with organic and conventional production systems that were evaluated from 2011 to 2013. The results showed that higher nitrogen mineralization was estimated using ISNT and DSD methodologies than with the Walkley-Black method, and that its content was different depending on the operating system. The best methodology The best methodology that quantified mineralization was Direct Steam Distillation (DSD); however for conventional systems sugarcane was Illinois Soil Nitrogen Test (ISNT), showing differences for the variables associated with the production and yield between the tested systems.